Implementasi Theory of Planned Behavior dan Risk Tolerance terhadap Intensi Investasi Peer to Peer Lending - Siti Mauidhoh Syarfi; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The purpose of this study is to determine the effect of attitude toward behavior, subjective norm, perceived behavioral control, and risk tolerance on investment intention of Surabayanese in peer to peer lending. This study is conclusive causality research with quantitative research data using a purposive sampling method and a random sampling method to get samples. Data in this study obtained by a questionnaire with a Likert scale. The sample used in this study were 200 Surabayas workforce. The analysis method used is multiple linear regression analysis using the SPSS program. The result is based on hypothesis testing that shows that attitude toward behavior and risk tolerance significantly influences investment intention. While the subjective norm and perceived behavioral control do not affect investment intention. It is because of the distribution respondents that dominated by young people that have age between 18-25 years. The respondents have a low belief in their social relations. It was also caused by respondents who have less information about fintech P2P lending which come up in Indonesia in 2016 and classified as a new type of investment.